Blei und seine Verbindungen – Bestimmung von δ‐Aminolävulinsäure in Urin mittels HPLC‐Fluoreszenzdetektion [Biomonitoring Methods in German language, 2018]. Issue 4 (19th October 2018) - Göen, T.; Weißflog, L.; Blaszkewicz, M.; Baumhoer, G.; Schettgen, T.; Dewes, P.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the presented biomonitoring method. The method described hereinafter permits the determination of δ ‐aminolevulinic acid (ALA) in urine as a biological marker of effect to assess exposure to lead. An indicator of such exposure is the increased urinary excretion of ALA caused by lead‐induced inhibition of the enzyme δ ‐aminolevulinic acid dehydratase. The determination of ALA in urine is based on a condensation reaction of ALA with formaldehyde and acetylacetone yielding a pyrrolizine derivate, which can be sensitively detected using fluorescence detection. 6‐Amino‐5‐oxohexanoic acid is used as an internal standard. Calibration standards are prepared in pooled urine and processed in the same way as the samples to be analysed. The method was extensively validated and the reliability data were confirmed by two independent laboratories, which have established and cross‐checked the whole procedure.